Temporal dynamics in zooplankton δ13C and δ15N isoscapes for the North Atlantic Ocean: Decadal cycles, seasonality, and implications for predator ecology - Espinasse, Boris; Sturbois, Anthony; Basedow, Sünnje L.; Hélaouët, Pierre; Johns, David G.; Newton, Jason; Trueman, Clive N. (Frontiers in Ecology and Evolution, 2022)
The limited amount of ecological data covering offshore parts of the ocean impedes our ability to understand and anticipate the impact of anthropogenic stressors on pelagic marine ecosystems. Isoscapes, i.e., spatial models of the distribution of stable isotope ratios, have been employed in the recent years to investigate spatio-temporal patterns in biogeochemical process and ecological responses. Development of isoscapes on the scale of ocean basins is hampered by access to suitable reference samples. Here we draw on archived material from long-running plankton survey initiatives, to build temporally explicit isoscape models for the North Atlantic Ocean (> 40°N). A total of 570 zooplankton samples were retrieved from Continuous Plankton Recorder archives and analysed for δ13C and δ15N values. Bayesian generalized additive models were developed to 1) model the relations between isotopic values and a set of predictors and 2) predict isotopic values for the whole of the study area. We produced yearly and seasonal isoscape models for the period 1998-2020. These are the first observation-based time-resolved C and N isoscapes developed at the scale of the North Atlantic Ocean. Drawing on the Stable Isotope Trajectory Analysis framework, we identify five isotopically distinct regions. We discuss the hydro-biogeochemical processes that likely explain theses modes, the differences in temporal dynamics (stability and cycles) and compare our results with previous bioregionalization efforts. Finally, we lay down the basis for using the isoscapes as a tool to define predator distributions and their interactions with the trophic environment. The isoscapes developed in this study have the potential to update our knowledge of marine predator ecology and therefore our capacity to improve their conservation in the future.